ANALYSIS OF PRIORITY BANKING OFFICER (PBO) MARKETING STRATEGY IN INCREASING THE NUMBER OF PRIORITY CUSTOMERS VIEWED FROM A MAQASHID SYARIAH PERSPECTIVE: BANK SUMUT KC SYARIAH PADANGSIDIMPUAN - Rambe, Jelita Handayani; Imsar, Imsar; Anggraini, Tuti (istinbath, 2024)
Maintaining the excellence of PT Bank Sumut KC Syariah Padangsidimpuan requires an effective marketing strategy to be implemented in order to realize a competitive advantage and achieve predetermined targets in the marketing process. Bank Sumut KC Syariah Padangsidimpuan certainly has goals and strategies with Sharia-based purposes (Maqashid Sharia) or is more than merely material. In this context, the target in question is Priority Customers. This writing analyzes the Priority Banking Officer's marketing strategy for increasing the number of priority customers at PT. Bank Sumut KC Syariah Padangsidimpuan is reviewed from a Maqashid Syariah perspective. The research method used is descriptive-qualitative. The data collection techniques in this research were observation, interviews, documentation, and literature. Moreover, researchers used descriptive analysis techniques. The result of this writing is that PT. Bank Sumut KC Syariah Padangsidimpuan, in implementing marketing strategies to increase the number of customers, applies the Marketing Mix 7P component. Marketing Mix is a tool for marketers consisting of various marketing program elements (product, price, promotion, place, people, process, and physical evidence) that must be considered to implement the determined marketing strategy. Bank Sumut KC Syariah Padangsidimpuan, in carrying out the marketing mix strategy, contains Maqashid Syariah principles containing sharia values ​​that are by sharia objectives (Maqashid Syariah). The marketing mix aspect (product, price, promotion, place, people, processes, and physical evidence) contains sharia values ​​by the 5 principles of maqashid sharia (sharia goals), namely protecting religion, soul, will, descendants, and property.